Minat mahasiswa akuntansi dalam memilih karir sebagai akuntan publik - Sriniyati; Erlinda Nur Khasanah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the influence of personality, intrinsic value of work, and financial rewards toward career intention as a public accountant. This research is a type of quantitative research. The data of this research was collected with the survey method. The survey was conducted using a questionnaire distributed to 98 Accounting major students of universities in the Special Region of Yogyakarta. The data analyses were conducted with linear regression analysis with SPSS 26 version. The results of this study indicate that: personality has a significant effect on a career intention as a public accountant, the intrinsic value of work has a significant effect on a career intention as a public accountant, and financial rewards have a significant effect on a career intention as a public accountant.